2014
DOI: 10.1590/s0102-053620140000400005
|View full text |Cite
|
Sign up to set email alerts
|

Doses of caffeine on the development and performance of pepper crops under greenhouse

Abstract: A number of experiments on plant organs demonstrated that caffeine acts as a growth stimulator. In this study we aimed to determine the influence of caffeine on development of pepper crops under stress in the autumn-winter cycle, as peppers stop growing and developing in November and January. The experiments were conducted to determine how caffeine applied to the soil by fertigation, with doses of 2.25 µM and 9.00 µM for T1 and T2, respectively, compared to the control crop, affect the morphological developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Previous studies of the effect of caffeine on a diversity of crops reported contradictory effects on plant growth, acting both as an enhancer or inhibitor of growth. This could be due to application of different caffeine concentrations, different periods of application, or examining effects on different plant organs (Montes et al 2014). Khanam et al (2000) reported that in Duboisia myoporoides tropane alkaloids were localized in the xylem cells of roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of the effect of caffeine on a diversity of crops reported contradictory effects on plant growth, acting both as an enhancer or inhibitor of growth. This could be due to application of different caffeine concentrations, different periods of application, or examining effects on different plant organs (Montes et al 2014). Khanam et al (2000) reported that in Duboisia myoporoides tropane alkaloids were localized in the xylem cells of roots.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiology of caffeine in plants is poorly understood. Several plant studies suggested that exogenous and/or endogenous caffeine may act as a growth enhancer, while others demonstrated its function as a plant growth inhibitor (Montes et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine, the other key component of the tea waste extract, can also degrade into xanthine and further urea (Mazzafera, 2002) just like xanthosine. Caffeine has already been recognized as a potential priming agent for seed germination (Ransom, 1912) and plant growth promoter as well, but there are mixed opinions (Montes, 2014).…”
Section: Possible Metabolic Breakdown Of Xanthosine and Caffeine In Twsmentioning
confidence: 99%
“…Several secondary metabolites are synthesized by the plants, including alkaloids, flavonoids, phenols, and terpenoids, which have major contributions to the adaptations of plants to their surroundings ( Montes et al., 2014 ). Alkaloids are specialized metabolites that influence numerous biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Purine alkaloids, well-known secondary metabolites, are often used as mild stimulants. A well-known alkaloid 1,3,7-trimethylxanthine, commonly known as caffeine, originated from purine, belongs to the xanthene family, and is naturally present in almost 100 plant species ( Montes et al., 2014 ). Caffeine is bitter, white, and crystalline in nature.…”
Section: Introductionmentioning
confidence: 99%